2019
DOI: 10.1007/s11340-018-00440-9
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Soft Tissues Mechanical Characterization: Volume-Based Aspiration Method Validated on Silicones

Abstract: Simulating the deformations of soft tissues has gained importance in recent years due to the development of 3D patient-specific biomechanical models in the context of Computer Assisted Medical Interventions. To design such models, the mechanical behavior of each soft tissue has to be characterized in-vivo. In this paper, a volume-based aspiration method for in-vivo mechanical characterization of soft tissues was validated on synthetic materials. For this purpose, two silicones with slightly different stiffness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The results of these two circuits are combined to provide the global pressurevolume curve (∆P tissue test − ∆V syringe test ). The general idea is that this curve can be transformed into the tissue pressure-volume curve (∆P tissue test − ∆V tissue i ) [20,38,39], where ∆V tissue i is the volume of tissue aspirated into the cup of suction diameter D i (figure 2 a and b).…”
Section: Cyclic Testing Devicementioning
confidence: 99%
See 2 more Smart Citations
“…The results of these two circuits are combined to provide the global pressurevolume curve (∆P tissue test − ∆V syringe test ). The general idea is that this curve can be transformed into the tissue pressure-volume curve (∆P tissue test − ∆V tissue i ) [20,38,39], where ∆V tissue i is the volume of tissue aspirated into the cup of suction diameter D i (figure 2 a and b).…”
Section: Cyclic Testing Devicementioning
confidence: 99%
“…Several attempts have been proposed to non-invasively identify mechanical properties of soft tissues in vivo [12,[16][17][18][19][20][21]. Suction-based set-ups, in particular, have received a lot of attention for the characterisation of the quasi-static mechanical response of the superficial soft in vivo [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done using homogenous silicone phantoms. Results obtained showed that errors in stiffness estimations remained below 7% (Elahi et al, 2019). The method has been used in a clinical pilot study to measure the tongue stiffness assuming an isotropic homogeneous material for tongue tissue (Kappert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the vacuum pressure, the portion of the tissue under the aperture is partially aspirated, with an amount of aspiration related to tissue stiffness. Our group recently proposed to use a light disposable aspiration system reduced to a simple tube 80 with a customisable (in size, shape and material) head aperture, able to meet any required severe sterilisation process (Elahi et al (2018); Elahi et al (2019); Connesson et al (2022) under review). This method, called VLASTIC, has been validated by comparing its estimations of synthetic material stiffness with the ones measured with classical experimental tensile tests.…”
Section: Introductionmentioning
confidence: 99%